Synergistic effect of sea cucumber saponins and EPA-enriched phospholipids on insulin resistance in high-fat diet-induced obese mice. Issue 7 (14th June 2019) - Han, Xiu-Qing; Zhang, Ling-Yu; Ding, Lin; Shi, Hao-Hao; Xue, Chang-Hu; Zhang, Tian-Tian; Wang, Yu-Ming
Abstract : The combination of sea cucumber saponins (SCS) and EPA-PL contributed to a synergistic effect on alleviating the obesity-related insulin resistance due to the amelioration of an inflammation centric peripheral insulin response. Abstract : Sea cucumber saponins (SCS) exhibit a significant effect on ameliorating glucose and lipid disorders by inhibiting fatty acid biosynthesis; however, high cytotoxicity and hemolytic activity limit their application. Eicosapentaenoic acid-enriched phospholipids (EPA-PL) significantly ameliorate insulin resistance and elevate the level of hepatic lipolysis, which may have a synergistic effect with SCS in alleviating obesity-related insulin resistance via multiple mechanisms. In the present study, high-fat diet-induced male C57BL/6J mice with obesity-related insulin resistance were used to evaluate the synergistic effect of SCS and EPA-PL on alleviating the insulin resistance. Results show that the combination of SCS and EPA-PL at a half dose exhibited a significant improvement on glucose intolerance and systematic insulin sensitivity than SCS or EPA-PL alone. Moreover, the half dose-combination remarkably inhibited the macrophage infiltration (F4/80) to white adipose tissue (WAT) and significantly down-regulated the level of MCP1, TNF-α and IL-6 compared with SCS and EPA-PL alone. Consequently, the combined administration not only decreased hepatic gluconeogenesis and increased hepatic glycogen synthesis ( P < 0.05), but also stimulated the glucose uptake in WAT and muscle ( P < 0.05). Nevertheless, neither SCS or EPA-PL alone exhibited any effect on the glucose uptake. The combination of SCS and EPA-PL contributed to a synergistic effect on alleviating the obesity-related insulin resistance due to the amelioration of an inflammation-centric peripheral insulin response.